Morphology and elemental composition of product obtained from struvite fluidized bed reaktor = Morfologia i skład chemiczny produktu odzysku fosforu w reaktorze z ruchomym złożem - Bydałek, Franciszek; Kula, Anna; Mąkinia, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Phosphorus scarcity is no longer a distant future, therefore the idea of phosphoru recovery is currently widely adopted and developed. Technologies based on the struvite precipitation are consider to address the future P challenges in the optimum way.
Keywords: phosphorus recovery; struvite; fluidized bed; odzysk fosforu; struwit; złoże ruchome